Knowledge Sharing System Berbasis Web (Studi Kasus: PDAM Tirta Musi Palembang) - Rian Pratama; Ruliansyah Ruliansyah; Muhamad Kadafi; Catur Eri Gunawan (Journal Of Informatics and Computer, 2020)
Perusahaan Daerah Air Minum (PDAM) Tirta Musi Palembang is a company engaged in providing mineral water services to the people of Palembang city. The company realizes the importance of managing and documenting employee knowledge for the sustainability of the company. Currently, the knowledge of employees at PDAM Tirta Musi Palembang has not been distributed properly, thus resulting in the ineffective utilization of this knowledge. The Knowledge Sharing System is a tool that can assist in documenting and distributing employee knowledge so that knowledge sharing can occur between employees. The purpose of this research is to build a Knowledge Sharing System that can be used to document and distribute employee knowledge. The system development method used in the Knowledge Sharing System is the Web Engineering method. This method is often used for web-based software development. The result of this research is that a web-based Knowledge Sharing System has been built which has been tested using the Black Box testing method and has been implemented at PDAM Tirta Musi Palembang which is used to assist in the management and documentation of employee knowledge.